132. Assessment of the Long-Term Effects of Training Consultant Pharmacists to Promote Antimicrobial Stewardship in Long-Term Care Facilities. (31st December 2020) - Ferguson, Claire; Chung, Philip; Lodhi, Hanan; Bergman, Scott; Cavalieri, R Jennifer; Neukirch, Alex; Ortmeier, Rebecca J; Rupp, Mark E; Rupp, Mark E; Van Schooneveld, Trevor C; Ashraf, Muhammad Salman
Abstract: Background: We implemented a one-year antimicrobial stewardship training program that lasted through 2018 where we assisted 9 long-term care facility (LTCF) consultant pharmacists in promoting antibiotic stewardship programs (ASP) in 32 LTCF (Figure 1). Surveys were conducted during and after the training program to assess performance. Methods: Infection Preventionists (IP), Directors of Nursing (DON) and Medical Directors (MD) of the LTCF received mail surveys in 2018 and online surveys in 2019. It included questions assessing the respondents' perceptions of their ASP, barriers to ASP implementation and stewardship related knowledge, and the skills and contributions of their consultant pharmacists. Qualitative analyses categorized reported barriers into common themes. Fisher exact test compared perceptions of consultant pharmacists' performance and frequently reported barriers during training and after the intervention was completed. Results: Representatives (IP, DON and/or MD) of 18 facilities responded to the surveys at both time points of the study, with 34 individual surveys in 2018 and 25 in 2019. Most rated their consultant pharmacists as knowledgeable and helpful who regularly provided feedback and suggestions both during and after the training (Table 1). Fifty-six percent of facilities reported that their consultant pharmacists were similarly involved, and 12% felt they were more involved, in ASP implementation in 2019 compared to 2018. Top 3 reported barriers to ASP implementations were the same during 2018 and 2019 (Table 2). Overall, 84% of facilities in 2019 believed that the consultant pharmacists "definitely helped" their ASP efforts, and 80% of facilities desired to continue the partnership into the future. Table 1. Comparison of Consultant Pharmacists' Performance Evaluations During (2018) and After (2019) Completion of Training Figure 3. Barriers to ASP implementation reported during (2018) and after (2019) training. Conclusion: This study demonstrates that training consultant pharmacists resulted in meaningful actions and prolonged engagement in ASP activities. Efforts should be directed on making similar training programs available nationwide for consultant pharmacists working in LTCF. Disclosures: Muhammad Salman Ashraf, MBBS, Merck & Co. Inc (Grant/Research Support)